Fraudulence and the competitive supply of public goods - Alfred Endres (Universität Konstanz, Fachbereich Wirtschaftswissenschaft und Statistik, 1978)
H. Demsetz claimed that under certain conditions private firms can supply public goods efficiently. Recently, it was argued that the optimality of the Demsetz equilibrium is destroyed when consumers engage in fraudulent behavior. In this paper, fraudulence is explicitly introduced in the Demsetz model. It ig shown that fraudulent consumers do no härm to the optimality of supplying public goods privately, within the framework of the Demsetz model.
Keywords: 330